2022
DOI: 10.3390/ijms23116213
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Investigation of the Plasma Proteome Associated with the Endotheliopathy of Trauma

Abstract: Background: The endotheliopathy of trauma (EoT) is associated with increased mortality following injury. Herein, we describe the plasma proteome related to EoT in order to provide insight into the role of the endothelium within the systemic response to trauma. Methods: 99 subjects requiring the highest level of trauma activation were included in the study. Enzyme-linked immunosorbent assays of endothelial and catecholamine biomarkers were performed on admission plasma samples, as well as untargeted proteome qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 264 publications
0
7
0
Order By: Relevance
“…The endothelium is located at the nexus of the blood and tissues and controls the transfer of O 2 , metabolic fuels, hormones, immune cells and factors, inflammatory regulators and fluids (96)(97)(98)(99)(100)(101)(102). Trauma-induced damage to this organ is termed the endotheliopathy of trauma (EoT), which is characterized by endothelial activation, vasoactivity, loss of barrier function, leukocyte adhesion, coagulopathy, inflammation and organ dysfunction (103)(104)(105)(106)(107)(108)(109)(110). In addition, the endothelium, like the BBB, is highly sensitive to changes in blood flow and shear stress, which can alter vascular tone, tissue perfusion, exchange and permeability (111).…”
Section: Second Pillar: the Endothelial Glycocalyxmentioning
confidence: 99%
See 1 more Smart Citation
“…The endothelium is located at the nexus of the blood and tissues and controls the transfer of O 2 , metabolic fuels, hormones, immune cells and factors, inflammatory regulators and fluids (96)(97)(98)(99)(100)(101)(102). Trauma-induced damage to this organ is termed the endotheliopathy of trauma (EoT), which is characterized by endothelial activation, vasoactivity, loss of barrier function, leukocyte adhesion, coagulopathy, inflammation and organ dysfunction (103)(104)(105)(106)(107)(108)(109)(110). In addition, the endothelium, like the BBB, is highly sensitive to changes in blood flow and shear stress, which can alter vascular tone, tissue perfusion, exchange and permeability (111).…”
Section: Second Pillar: the Endothelial Glycocalyxmentioning
confidence: 99%
“…In 2017, Johansson and colleagues introduced a model of SHock-INduced Endotheliopathy (SHINE) to better understand the underlying pathophysiological mechanisms for critically ill patients (147). Like SHOT, they propose that shockinduced sympatho-adrenal hyperactivation is a critical driver of endothelial cell and glycocalyx damage, hypoperfusion, and 10.3389/fmed.2022.968453 subsequent hemostatic aberrations and multiorgan dysfunction (110). More recently, Henriksen reported that patients with identical trauma severity developed significantly different degrees of endothelial dysfunction, as measured by syndecan-1, and proposed a minimum of four shock-induced endotheliopathy phenotypes (148) with the differences most likely driven by a genetic component (148).…”
Section: Other Unifying Models Of Traumatic Injurymentioning
confidence: 99%
“…Additional recent data show that EoT is a pathophysiologic state that persists over the first 24 hours after injury and remains a significant predictor of poor outcomes throughout this time period. 14 Using innovative proteomics approaches, Krocker et al 15 have shown that EoT is associated with a unique plasma proteome signature enriched in damage-associated molecular patterns (DAMPS), inflammatory mediators, and organ-specific intracellular markers, corroborating clinical evidence linking EoT with organ damage.…”
Section: Postinjury Morbidity and Mortality Linked To Eotmentioning
confidence: 89%
“…Proteomic profiling may be the next generation of understanding trauma-related pathways and biomarkers. Krocker et al explored a set of proteins that best predict endotheliopathy (SDC-1 ≥ 40 ng/mL) and end-organ damage in a cohort of severely injured patients (128). On proteomic analysis, they found 52 proteins differentially expressed between the groups, with the top 10 strongly predictive for endotheliopathy.…”
Section: Proteomicsmentioning
confidence: 99%
“…On proteomic analysis, they found 52 proteins differentially expressed between the groups, with the top 10 strongly predictive for endotheliopathy. Of note, four DAMP proteins were found to have elevated concentrations in the endotheliopathy of trauma group, which have been shown to mediate a multitude of endothelial impairment and permeability, inflammatory responses, and end-organ injury (128). Li et al (129) conducted a secondary analysis of trauma patients included in the Prehospital Air Medical Plasma and Study of Tranexamic Acid During Air and Ground Medical Prehospital Transport trials using high-dimensional proteomics.…”
Section: Endothelial Targeted Therapies and Future Directionsmentioning
confidence: 99%